A Case Report of Successful Conservative Treatment for Infective Endocarditis Caused by Gemella sanguinis - Georgia Emmanouilidou; Panagiota Voukelatou; Ioannis Vrettos; Vasileia Aftzi; Konstantinos Dodos; Despoina Koumpouli; George Avgeropoulos; Andreas Kalliakmanis (Case Reports in Infectious Diseases)
Infective endocarditis is defined as an infection of a native or prosthetic heart valve, the endocardial surface of the heart, or an indwelling cardiac device. Among the miscellaneous emerging opportunistic bacteria that can cause infective endocarditis is Gemella sanguinis that has been reported as a cause of infective endocarditis in nine cases in the past. All of the survivors received antimicrobial therapy and underwent prosthetic valve replacement surgery while, in general, a proportion of 40–50% of the patients with infective endocarditis underwent valve surgery. Our case illustrates that valve surgery, in combination with the administration of antibiotics, is not the only therapeutic option for infective endocarditis due to Gemella sanguinis and that a conservative management with prolonged administration of parenteral antibiotics under close supervision of the patient can be an option.